2002
DOI: 10.1007/s00234-002-0806-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of water in large demyelinating lesions: a follow-up study

Abstract: We studied five patients with multiple sclerosis with one plaque of demyelination more than 2 cm in diameter, using conventional and diffusion-weighted MRI, soon after the onset of symptoms and over 1-36 months. The orientationally averaged diffusion coefficient was increased in all the acute lesions, and increased further during follow-up in three. There was a strong correlation between and the degree of low signal on T1-weighted images. The quantitative information provided by allowed delineation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…Several reports have demonstrated increased ADC values both in acute contrast-enhancing and chronic MS lesions as well as in the NAWM, confirming that diffusion measurements are sensitive for detecting pathologic changes associated with states of increased water mobility. [3][4][5]8,18 In chronic MS lesions, the ADC increase is highly variable (most pronounced ADC increase in T1 hypointense lesions) and higher than that in NAWM; this finding confirms the concept that the severity of tissue matrix damage of MS lesions is heterogeneous. 8 It has been suggested that inflammatory vasogenic edema, axonal loss, and demyelination are the most likely pathologic substrates of increased ADC.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Several reports have demonstrated increased ADC values both in acute contrast-enhancing and chronic MS lesions as well as in the NAWM, confirming that diffusion measurements are sensitive for detecting pathologic changes associated with states of increased water mobility. [3][4][5]8,18 In chronic MS lesions, the ADC increase is highly variable (most pronounced ADC increase in T1 hypointense lesions) and higher than that in NAWM; this finding confirms the concept that the severity of tissue matrix damage of MS lesions is heterogeneous. 8 It has been suggested that inflammatory vasogenic edema, axonal loss, and demyelination are the most likely pathologic substrates of increased ADC.…”
Section: Discussionmentioning
confidence: 57%
“…1 Two longitudinal studies that also used longer intervals between MRI examinations (minimum of 4 weeks) have observed increased ADC signal intensity in the lesions already at the first MRI. 5,6 We think that both patient selection and the time from symptom onset to the first MRI are important in this regard and that it might well be that the hyperacute phase was missed in these studies. Another cross-sectional study extrapolated different phases of lesion acuity by using DWI findings; however, this was done without the opportunity to ascertain DWI findings on serial analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute multiple sclerosis plaques typically demonstrate increased diffusion-weighted signal with increased ADC values [37,70,71]. As the plaques age, the ADC values decrease but remain elevated compared with normal white matter [72][73][74].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…This well recognized imaging pattern is felt to represent increased free water content due to vasogenic edema and demyelination. 1 Rarely, MS lesions have increased DWI and decreased ADC signal in the acute phase, a pattern that mimics the radiographic features of acute stroke. [2][3][4] Such diverse disorders as primary central nervous system lymphoma, abscess, hemorrhage, and post-stroke Wallerian-like degeneration can also have true restricted diffusion.…”
mentioning
confidence: 99%